The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4103/0974-8490.99072
|View full text |Cite
|
Sign up to set email alerts
|

Vitex negundo inhibits cyclooxygenase-2 inflammatory cytokine-mediated inflammation on carrageenan-induced rat hind paw edema

Abstract: Background:Vitex negundo L. (Verbenaceae) is a hardy plant widely distributed in the Indian subcontinent and used for treatment of a wide spectrum of health disorders in traditional and folk medicine, some of which have been experimentally validated. In present study, we aimed to investigate the anti-inflammatory effects of V. negundo in carrageenan-induced paw edema in rats, and to investigate the probable mechanism of anti-inflammatory action.Materials and Methods:Paw edema was produced by injecting 1% solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Paw edema induced by carrageenan is an acute model of inflammation widely used to evaluated anti-inflammatory effect of natural products. [ 31 32 33 ] After injection, carrageenan immediately produces edema, hyperalgesia, and erythema, resulting from the action of proinflammatory agents such as bradykinin, histamine, tachykinins, and complement. [ 34 ] Our results showed that all extracts present anti-inflammatory effects, being GOJI extract more effective in reducing paw edema than BLUE and CRAN extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Paw edema induced by carrageenan is an acute model of inflammation widely used to evaluated anti-inflammatory effect of natural products. [ 31 32 33 ] After injection, carrageenan immediately produces edema, hyperalgesia, and erythema, resulting from the action of proinflammatory agents such as bradykinin, histamine, tachykinins, and complement. [ 34 ] Our results showed that all extracts present anti-inflammatory effects, being GOJI extract more effective in reducing paw edema than BLUE and CRAN extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stopping the releasing of COX and inhibiting the production of prostaglandins, is a vital way to prevent inflammatory response. [8] Guay, et al found that the stimulation of COX-2 that occurs in the central nervous system during carrageenaninduced paw inflammation leads to an elevation in PGs, prostacyclin and TX in the early phase and to a large increase in PGE2 production linked to selective up-regulation of mPGES-1. [20] Our results showed that injection of Cg caused elevation of the mean of all inflammatory markers as COX-2, PGE 2 with high significant value (0.001) in comparison with the means of these markers in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Group): Eight mice injected with 200 μl of 1% solution of carrageenan in saline into the left hind paw and into trunk region subcutaneously under light ether anaesthesia. [8] After 15 min observing the swelling in left hind paw at the inflammation site. Group III (Carrageenan+Metformin group) (Cg.…”
Section: Biochemical Estimation Of Mda Sod and Gsh In The Livermentioning
confidence: 99%
See 2 more Smart Citations